A gramática de participação do diretor de escola na administração de recursos financeiros em escolas públicas da cidade de São Paulo - Kubo, Gisele Pereira (2021)
The present work consists of investigating how the school principal participates in the administration of financial resources in public schools in the city of São Paulo. The research question that guides this dissertation is how is the grammar of participation of the school principal in the use and application of public funds received and collected by the educational unit? We start from the hypothesis that the paths of money that have the purpose of financing public education in the city of São Paulo are complex and legally organized, but the procedures for the management of resources do not comply with the principles of decentralization of funds - those of management participatory - which, in practice, is not effective, since the funds destined to the units are already determined for use and the centralized resources do not count on the network's participation in the destination. The general objective is to understand the management of education financing in the city of São Paulo, with an emphasis on the grammar of participation of the school principal. The specific objectives are: to detail the grammar of the school principal's participation in the administration of decentralized public funds to educational units and to list the basis for discussion material for the school principal regarding the functioning of education financing, consistent with principles of participation. Starting from these objectives, the research was developed through a qualitative approach, with a history of oral life of school principals. The research subjects are five school principals, one of whom is retired from a career. The collected data were examined through discourse analysis and the theoretical framework adopted was the Frankfurt School Critical Theory, especially the thinking of Theodor Adorno, Max Horkheimer and Herbert Marcuse, in addition to contemporary scholars who continue the reflections of these three thinkers in their studies. After the empirical procedures, the contradictions between a decreed grammar became evident, with the requirements imposed by legislation, regarding the role of the director in the management of financial resources, which limit his role to an administrative assistant of the central organ, as well as revealed himself the director's participation grammar, which is tutored and critical. Guarded when it occurs through adaptation and criticism, even if superficially, which mobilizes the creation of proper strategies for the use of financial resources, even in the face of so many ties and bureaucratic processes. As an intervention proposal, we list three points for the organization and preparation of discussion material for the directors, namely: approach to the functioning of education financing (fund policy, own resources and education salary); contextual training and review of official documents on the director's role, collectively, electing work guidelines and principles, with a focus on work autonomy.